Product's country of origin: method and approaches - Yassin, Ammar (Penerbit UTM Press, 2009)
Starting with our formative years and throughout our lives, we form images of countries around the world through education, friends, products and other experiences. These images of the country of origin and factors such as brand, warranty and price influence the way we think and act during product evaluation (Papadopoulos, 1993). As a reflection of the emerging importance of the country of origin phenomena, a stream of theoretical and empirical research has provided a wealth of knowledge on the direct use of COO effect, or the so-called “made-in” label. This paper discussed the literature review of product’s country of origin effects.